Shahrukh Rafi Khan. Government, Communities, and Non-Governmental Organisations in Social Sector Delivery: Collective Action in Rural Drinking Water Supply. Aldershot, UK: Ashgate Publishing Ltd., 1999. 144 pages. Hardbound. Price not given. (The Pakistan Development Review, 2000)
Shahrukh Rafi Khan’s book comprises three chapters and 15 appendices— eight appendices attached with Chapter Two and the remaining with Chapter Three. The book contains around twelve tables. The case studies included by the author facilitate further insights into the sustainability of the schemes. Chapter One gives an overview of the philosophy, important concepts, and salient features of participatory development (PD). Khan explains the various approaches and methodologies developed and/or followed by different Non- Government Organisations (NGOs). He is of the opinion that the Agha Khan Rural Support Programme (AKRSP) followed an integrated development approach which paved the way to sustainability. The author also explains the alternate strategy to development that is practised by the Sungi Foundation. He also illustrates the lessons/experiences of various institutions/organisations in the field of PD. The author believes that the strength of PD is that it is complementary to both the state and the market.